Investigation of Knowledge Sharing Behavior in Global Software Development Organizations Using Social Cognitive Theory - Anwar, Rayhab; Rehman, Mobashar; Wang, Khor Siak; Hashmani, Manzoor Ahmed; Shamim, Amjad (IEEE access, 2019)
Software development is a cooperative process, which relies upon the integration of knowledge spread across various domains. The shift from the industrial economy toward a decentralized knowledge-based economy has given knowledge more value and importance for organizations, which operate globally. Management of knowledge sharing activities becomes challenging and complex, specifically when operating in a globally distributed organization. The impact of "personal factors" and "environmental factors" on software developers with regard to knowledge sharing behavior in global software development organizations is an important subject, which is still not well discussed. The social cognitive theory has been utilized in the formation of the conceptual model with a focus on knowledge sharing behavior. This paper examines the impact of key factors, including "time zone difference," "geographic distance," "linguistic distance," "trust," "motivation," and "social interaction" on knowledge sharing behavior. Self-administrative postal and online questionnaire were used as the medium of data collection. It was found that "social interaction" had the strongest impact on knowledge sharing behavior.